Evaluation of Soil Nutrient Status of Dargahan Village of Kanker District of Chhattisgarh - Kodopi, Monika; Bachkaiya, Vinay; Patel, Yamini (International Journal of Economic Plants, 2025)
The study was conducted during the kharif season (June–November, 2024) in Dargahan village, Kanker district, Chhattisgarh, India to assess the soil fertility. A total of 145 soil surface samples (0–15 cm) were collected. The samples were analyzed for pH, electrical conductivity (EC), organic carbon (OC), macronutrients (N, P, K, S), and micronutrients (Fe, Mn, Cu, Zn, B). The soil pH ranged from 4.33 to 7.57, with a mean of 5.56, indicating Strongly acidic to neutral soil. EC ranged from 0.03 to 0.9 dS m-1 (mean 0.12 dS m-1), suitable for all crops. OC varied from 3.1 to 8.0 g kg-1, with 49% classified as low, 50% as medium, and 1% as high. Nitrogen (N) levels were low, ranging from 100.35 to 263.42 kg ha-1 (mean 173.88 kg ha-1). Phosphorus (Olsen P) ranged from 8.6 to 37.5 kg ha-1 while Phosphorus (Bray P-1) ranged from 20.35 to 67.89 kg ha-1 ( mean 45.44 kg ha-1), and potassium ranged from 107.29 to 547.68 kg ha-1 (mean 190.53 kg ha-1). Sulfur content ranged from 18.16 to 39.76 kg ha-1 (mean 28.34 kg ha-1). Micronutrients showed varying levels: Fe ranged from 5.44 to 42.43 mg kg-1 (mean 25.24 mg kg-1), Mn from 2.06 to 21.17 mg kg-1 (mean 9.67 mg kg-1), Cu from 0.81 to 2.9 mg kg-1 (mean 1.64 mg kg-1), Zn from 0.12 to 0.96 mg kg-1 (mean 0.36 mg kg-1), and B from 0.14 to 1.77 mg kg-1 (mean 0.75 mg kg-1). According to the nutrient index value (NIV), the soils were low in N and Zn, medium in P, K, S, and B, and high in Fe, Mn, and Cu.